KEMAMPUAN DAYA TETAS TELUR (Hatching Rate) IKAN PATIN (Pangasius Hypophthalmus) DALAM AQUARIUM DENGAN PERLAKUAN TEMPERATUR YANG BERBEDA - Mukhlisah (Chlorophyl, 2022)
Catfish (Pangasius hypopthalmus) culture is very potencial to be develop. One of the critical success factors is the success of cultivition is the availability of good a seeds in sufficient quantities and sustainable. Temprature is one of the factors that influence the hatch ability of eggs. The experiment used a completly randomized design (CRD) method, consisting of three treatments and three replications. The order of treatment was A 27˚C, B 29˚C dan C31˚C. The result of research for each treatment A, B, and C indicate that avarage of hatching rate ware 67%, 68% and 71%. Data analysis uses variance test (ANOVA). The result showed the temperature did not significantly